2021
DOI: 10.1111/1556-4029.14962
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of simulated clandestine graves of dismembered victims using UAVs, electrical tomography, and GPR over one year to aid investigations of human rights violations in Colombia, South America

Abstract: In most Latin American countries, there are significant numbers of missing people and forced disappearances, over 120,000 in Colombia alone. Successful detection of shallow buried human remains by forensic search teams is difficult in varying terrain and climates. Previous research has created controlled simulated clandestine graves of murder victims to optimize search techniques and methodologies. This paper reports on a study on controlled test site results over four simulated dismembered victims’ clandestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…This is a unique finding because other published research, such as Molina et al. [61], has shown that burials with clothed victims are imaged better than those who are buried naked because the clothing acts as a target surface for the electromagnetic waves.…”
Section: Resultsmentioning
confidence: 78%
“…This is a unique finding because other published research, such as Molina et al. [61], has shown that burials with clothed victims are imaged better than those who are buried naked because the clothing acts as a target surface for the electromagnetic waves.…”
Section: Resultsmentioning
confidence: 78%